Association between sleep duration during pregnancy and gestational diabetes mellitus: a systematic review and meta-analysis - Li, Yuandong; Liang, Chao; Wu, Cui; Nan, Zheng (Frontiers in Medicine, 2024)
Objective To systematically review studies on the correlation between sleep duration during pregnancy and gestational diabetes mellitus (GDM) and use meta-analysis to explore the correlation between the two to provide a basis for preventing GDM during pregnancy. Methods The search databases were China Knowledge Network (CNKI), Weipu, Wanfang, China Biomedical Literature Service System (SinoMed), Cochrane Library, Web of Science, Embase, and PubMed, and the search time was from the establishment of the above databases to July 2023. The data were statistically analyzed using STATA/MP17 and RevMan 5.3 software. Publication bias could be accurately assessed using funnel plots and Egger’s test. Results A total of 5,197 papers were searched, and 13 studies were finally included, which included 80,259 individuals, including 3,461 patients with GDM. The comprehensive analysis showed that. Based on pooled data from prospective, cross-sectional, and case–control studies, extreme sleep duration during pregnancy was strongly associated with GDM compared with average sleep duration. The results of the prospective studies showed that both short (OR = 1.50, 95% CI: 1.07–2.10, I2 = 60.9%, p = 0.02) and long (OR = 1.28, 95% CI: 1.13–1.46, I2 = 0.0%, p < 0.0001) sleep duration increased the risk of gestational diabetes mellitus, but the harms were more pronounced with short sleep. In analyzing the association between extreme sleep duration and GDM, publication bias was found in prospective, cross-sectional, and case–control studies with moderate heterogeneity and prospective-only studies with low heterogeneity. Conclusion Both too short and too long sleep duration during pregnancy are strongly associated with GDM. Either too short or too long sleep duration predicts the risk of developing GDM, but the harms are more pronounced with short sleep. These findings remind us of the importance of controlling sleep duration during pregnancy and help to optimize early strategies to prevent GDM. Systematic review registration: http://www.crd.york.ac.uk/prospero, identifier [CRD42023470925].